2007
DOI: 10.1590/s0066-782x2007000400015
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensão arterial e alguns fatores de risco em uma capital brasileira

Abstract: SummaryObjectives: Estimate the prevalence of hypertension and some cardiovascular risk factors in the adult population of a major city in Brazil.Methods: Descriptive, observational, transversal population-based study substantiated by the home survey of a simple random sample (>18 years old). Standardized questionnaires were used to obtain sociodemographic information, measurements of blood pressure (2 measurements), weight, height, and abdominal circumference (AC). Microsoft Access and Epi Info 6 were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
61
1
53

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 18 publications
12
61
1
53
Order By: Relevance
“…Confirming this evidence, Pitanga and Lessa 31 observed that physically active adults during leisure time had lower levels of SBP and DBP. At the same time, a study estimated the prevalence of AH and some of its risk factors in Goiânia, Goiás, and observed that moderate or intensive physical activity during leisure time and mild physical activity at work presented a negative association with the occurrence of AH 3 . Considering physical activities of locomotion, Hayashi et al 32 investigated the association between time of walk to work and physical activity during leisure time with the risk of AH and found 12% less risks of becoming ill when the time of walk increased 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Confirming this evidence, Pitanga and Lessa 31 observed that physically active adults during leisure time had lower levels of SBP and DBP. At the same time, a study estimated the prevalence of AH and some of its risk factors in Goiânia, Goiás, and observed that moderate or intensive physical activity during leisure time and mild physical activity at work presented a negative association with the occurrence of AH 3 . Considering physical activities of locomotion, Hayashi et al 32 investigated the association between time of walk to work and physical activity during leisure time with the risk of AH and found 12% less risks of becoming ill when the time of walk increased 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial hypertension (AH) is a chronic disease in charge of the increasing risk of fatal and non-fatal cardiovascular events, which contributes to the high demand in urgency and emergency sectors and primary health care services [1][2][3] . Since it is characterized as a multifactorial clinical condition, the disease requires special attention in the identification of associated comorbidities or risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…b Some factors are important in the determination of arterial hypertension, like excess weight, which has been frequently reported in the scientific literature. 10,12 Other factors include: smoking, which causes the activation of the sympathetic nervous system, oxidative stress and vasoconstrictive effect associated with the increase in inflammations related to hypertension; 3 alcohol consumption, which has been associated with an increase in hypertension prevalence, probably due to the fact that it has a direct harmful action on the cardiac muscle. 6 On the other hand, physical activity, at high and regular levels, tends to reduce blood pressure values.…”
Section: Introductionmentioning
confidence: 99%
“…12 Several studies recommend establishing campaigns to promote healthy habits and changes in behavior in pupils, and others emphasize the importance of educating this population on the risk factors for chronic non-communicable illness and measures for avoiding these illnesses. 1,6,11,15 The PVS sought to promote permanent educational campaigns for teachers and health care professionals, and events promoting health in the partner school communities approaching topics concerned with healthy habits and citizenship through active methodologies. 4 However, studies show that merely establishing policies does not promote change, the dimension of the choices needs to be taken into account, in the case of diet, as well as the use of qualitative strategies, to redeem concepts, beliefs and individual and group behavior.…”
Section: Discussionmentioning
confidence: 99%